Nurses' Dorm - (:unkn) unknown (Coy C. Carpenter Library, 1948)
Published in 1948 Gray and White Matter yearbook.
Five student nurses at North Carolina Baptist Hospital are relaxing in the nurses' dorm as they discuss and gather information for the 1948 "Placebo" publication. Pictured in no specific order: Mary Emma Rhodes, Editor; Jeanne Hollowell, Art; Jean Ray, Features; Carrie Bridges, Circulation; and Evelyn Beasley.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth